Engaging minds through animation: The effectiveness of 2D content in medical health education - Parumo, Shahril; Rahim, Sarni Suhaila; Chia, Yen Toh Darren; Abd Samad, Rosleen; Jali, Suriati Khartini (Little Lion Scientific Islamabad Pakistan, 2025)
The article examines the effectiveness of 2D animated content as an engaging and innovative educational tool for mental health education. The study explores how such animations can enhance understanding and raise awareness of mental health disorders among diverse audiences. Among the ongoing difficulties mental health education faces are stigma, misunderstandings, and a dearth of interesting materials that successfully explain difficult disorders like bipolar disease. To this end, six user-friendly animated modules were developed, focusing on key aspects of Bipolar Disorder, including an introduction to the condition, its symptoms, causes, prevalence, types, and available treatments. A structured evaluation process was employed, combining usability testing to measure knowledge retention with participant feedback to capture perceptions and experiences. The study engaged three target groups: healthcare professionals, multimedia experts involved in content creation, and members of the general public with varying levels of familiarity with Bipolar Disorder. By integrating insights from these groups, the research highlights the transformative potential of 2D animation in mental health education. Preliminary findings demonstrate that animated content significantly improves comprehension and awareness, presenting it as a dynamic, engaging, and accessible medium for disseminating information. These results underscore the promise of 2D animation in reducing stigma and misconceptions about mental health disorders, paving the way for the development of future educational resources and interventions.